(untitled) (Research, Society and Development, 2020)
The present work aims to present the contributions to learning by using Scientific Dissemination Texts (TDC) of Environmental Education in Chemistry Teaching. The work was developed during the Pedagogical Residency Program of the Degree in Exact Sciences at the Federal University of Pampa, campus Caçapava do Sul / RS during the second semester of 2019 and was applied in a rural school in the municipality. Based on the theoretical frameworks used in this research, the use of TDCs as a resource to improve teaching and learning processes can bring advantages in understanding scientific meanings, since TDCs generally use an updated language, making the text easy to understand to the reader. The research is of a qualitative nature in which three categories of analysis emerged from the data analysis: (i) Potentialities of text interpretation in working with TDC, (ii) Difficulties with the scientific concept in TDC and, (iii) Strategies used in the work with TDC. In this article, the first category will be discussed, and the others will be analyzed in another document. From the didactic experience, it can be verified that the use of TDC, once worked in conjunction with the Environmental Education theme, can corroborate so that students have a better perception of the scientific aspects involved in the environmental and daily context and a better awareness of the use of natural resources.